Smart kindergarten classroom with the help of IoT - Nur Anis Hannani Binti Suhaimi; Intan Izyan Binti Roslan (Global Econedu, 2025)
With the introduction of the smartphone, life has become more convenient, leading to the emergence of a new research topic called the Internet of Things. Due to the advancement of technology, it is now common to remotely connect with your everyday interactive device using a portable device such as a Smartphone with internet access, leading to billions of devices currently benefiting from this capability. This paper describes the implementation of a system that simplifies communication within kindergarten classrooms by using automation and security measures with the assistance of the Internet of Things. The system allows individuals to remotely monitor and control certain areas of a classroom from any location. There are different methods for automating your classroom, including automatic lighting and fans, smart projectors, smart water purifiers, and more. Savings of just a few minutes each day lead to a rapid return on investment in terms of both real costs and better student results. Thanks to advanced automation and wireless technology, all the devices in the classroom can now be connected to the internet. This enhances the energy support skill, indoor safety, and cost savings for the classroom. The presence of a person in the classroom can be detected by using an IR Sensor. The sensor emits a signal and detects the signal as it bounces back from the person. The duration of the emission and reception assists the IR sensor in determining the distance between individuals.